-6+ -6- -2
Adding a negative is the same as subtracting a positive.
-6 - 6 - -2
Subtracting a negative is the same as adding a positive.
-6 - 6 + 2
Subtracting a number from a negative number is like adding the positive numbers, just remember to put the negative sign in front of the number.
-12 + 2
Adding a positive number to a negative number is like subtracting a positive from another positive, but don't forget the negative sign when you're done.
-12 +2 = -10
Answer:
the answer would be 2x^2-4x
Answer:
x=-2
Step-by-step explanation:
(2/3)^x-1=27/8
Rewriting the right hand side
(2/3)^x-1=(3/2)^3
We know that a^-b = 1/a^b Hint: { 1/(3/2) = 2/3}
(2/3)^x-1=(2/3) ^-3
The bases are the same, so the exponents are the same
x-1 = -3
x -1+1 = -3+1
x = -2